2
$\begingroup$

I'm solving an exercise and I'm asked to prove that if

$$u_n = \left(1+\frac{1}{n^2}\right)\left(1+\frac{2}{n^2}\right)\left(1+\frac{3}{n^2}\right)\ldots\left(1+\frac{n}{n^2}\right)$$

then $\lim u_n = \sqrt{e}$.

This is after it asks me to show that $\forall x>0,$

$$x-\frac{1}{2}x^2<\ln(1+x)<x$$

which I did, but even with this result I'm not being able to even get how to use it to show $\lim u_n = \sqrt{e}$.

$\endgroup$
  • 3
    $\begingroup$ Given the inequality, you may be tempted to take logarithm to obtain $$ \sum_{k=1}^{n} \frac{k}{n^2} - \frac{k^2}{2n^4} < \log u_n < \sum_{k=1}^{n} \frac{k}{n^2}. $$ Can you proceed from here? $\endgroup$ – Sangchul Lee Mar 18 '18 at 20:51
  • 1
    $\begingroup$ Yes! I was absolutely forgetting about the log properties to transform the sum into product. $\endgroup$ – Concept7 Mar 18 '18 at 21:01
2
$\begingroup$

$$\ln (u_n)=\sum_{k=1}^n\ln (1+\frac {k}{n^2} )$$ but for $k=1,2...n,$

$$\frac {k}{n^2}-\frac {k^2}{2n^4}<\ln (1+\frac {k}{n^2})<\frac {k}{n^2} $$

sum these inequalities and use the identities $$\sum_{k=1}^n\frac {k}{n^2}=\frac {n (n+1)}{2n^2} $$ and $$\sum_{k=1}^n\frac {k^2}{n^4}=\frac {n (n+1)(2n+1)}{6n^4} $$ Do not forget to squeeze.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.